Paracoccidioides brasiliensis interferes on dendritic cells maturation by inhibiting PGE(2) production - Fernandes, Reginaldo K. [UNESP]; Bachiega, Tatiana F. [UNESP]; Rodrigues, Daniela R. [UNESP]; Golim, Marjorie de A. [UNESP]; Dias-Melicio, Luciane A. [UNESP]; Balderramas, Helanderson de A. [UNESP]; Kaneno, Ramon [UNESP]; Soares, Angela M. V. C. [UNESP] (Public Library Science, 2015)
Paracoccidioidomycosis (PCM) is a systemic mycosis, endemic in most Latin American countries, especially in Brazil, whose etiologic agent is the thermodimorphic fungus of the genus Paracoccidioides, comprising cryptic species of Paracoccidioides brasiliensis, S1, PS2, PS3 and Paracoccidioides lutzii. The mechanisms involved in the initial interaction of the fungus with cells of the innate immune response, as dendritic cells (DCs), deserve to be studied. Prostaglandins (PGs) are eicosanoids that play an important role in modulating functions of immune cells including DCs. Here we found that human immature DCs derived from the differentiation of monocytes cultured with GM-CSF and IL-4 release substantial concentrations of PGE2, which, however, were significantly inhibited after challenge with P. brasiliensis. In vitro blocking of pattern recognition receptors (PRRs) by monoclonal antibodies showed the involvement of mannose receptor (MR) in PGE2 inhibition by the fungus. In addition, phenotyping assays showed that after challenge with the fungus, DCs do not change their phenotype of immature cells to mature ones, as well as do not produce IL-12 p70 or adequate concentrations of TNF-alpha. Assays using exogenous PGE2 confirmed an association between PGE2 inhibition and failure of cells to phenotypically mature in response to P. brasiliensis. We conclude that a P. brasiliensis evasion mechanism exists associated to a dysregulation on DC maturation. These findings may provide novel information for the understanding of the complex interplay between the host and this fungus.